ANALYSIS OF THE DEVELOPMENT PROCESSES OF THE TOURISM SECTOR IN QASHQADARYO REGION DURING THE YEARS OF INDEPENDENCE (International journal of artificial intelligence, 2025)
This article analyzes the development processes of the tourism sector in the Kashkadarya Region during the years of independence. It examines the region's natural and cultural heritage, the development of tourism infrastructure, the opening of new tourist destinations, and the government support measures implemented. The article also analyzes the role of the tourism sector in economic and social development and its contribution to the region's sustainable development.